DIALEKTIKA KEMAJUAN PENDIDIKAN: STUDI IMPLEMENTASI KURIKULUM PARADIGMA BARU DALAM PEMBELAJARAN SOSIOLOGI DI SMA NEGERI 4 MAKASSAR - Handayani, Ade; Kaharuddin, Kahaaruddin; Yumriani, Yumriani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
A number of pros and cons still continue to follow the discourse on the practice of implementing the new paradigm curriculum (Kurikulum Merdeka) in Indonesia. Problems, both conceptual and technical, are related to the practice of the new curriculum which, therefore, creates differentiated practice. Qualitative research from this type of case study is a specific contribution that focuses on the practice of implementing the Merdeka curriculum in Social Sciences learning at the Upper Middle School level (SMA Negeri 4) Makassar City. A total of 35 informants were interviewed to get a specific picture regarding the implementation practices of the new curriculum; Thematic analysis of the interview results was carried out to identify and further, classify various possibilities – both driving and inhibiting factors. The results show that although the practice of implementing the new curriculum is still less than optimal, we note several things that are important to consider - both by a number of educational institutions, as well as educational practitioners, as well as intellectuals-academics in general in considering the relevance of curriculum implementation practices.